2017
DOI: 10.1002/oby.22054
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Barriers to Effective Obesity Care: Results from the National ACTION Study

Abstract: Objective: ACTION (Awareness, Care, and Treatment in Obesity maNagement) examined obesity-related perceptions, attitudes, and behaviors among people with obesity (PwO), health care providers (HCPs), and employer representatives (ERs). Methods: A total of 3,008 adult PwO (BMI 30 by self-reported height and weight), 606 HCPs, and 153 ERs completed surveys in a cross-sectional design. Results: Despite several weight loss (WL) attempts, only 23% of PwO reported 10% WL during the previous 3 years. Many PwO (65%) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

18
217
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 230 publications
(265 citation statements)
references
References 22 publications
18
217
1
3
Order By: Relevance
“…In both studies, 44% of patients believe that it is their responsibility to manage their weight with most acknowledging lifestyle change as necessary 21. Many findings of the current study were similar to those of ACTION.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…In both studies, 44% of patients believe that it is their responsibility to manage their weight with most acknowledging lifestyle change as necessary 21. Many findings of the current study were similar to those of ACTION.…”
supporting
confidence: 65%
“…[8][9][10][11][12][13][14][15] Data on bleeding tendency in obese PwH are largely inconclusive; however, some individuals may experience reduced joint bleeds following moderate weight loss. 21 PwO and HCPs in ACTION generally reported that the most frequent strategies employed were general recommendations to eat less and to be more active. 18,19 Conventional weight-based dosing of factor replacement leads to increased costs for people with haemophilia and obesity (PwHO), suggesting pharmacoeconomic benefits of weight loss.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of building healthy therapeutic relations between patients and healthcare providers was demonstrated in a recent study that assessed patient perspectives in the role of primary care in obesity management [9]. Also, another recently published study revealed divergence in perception and attitudes between patients with obesity and HCP’s perspective of obesity treatment [10]. Although assessments of psychological issues are considered essential for the identification of the optimal treatment choice at an individual level, the influence of an individual’s psychological health on obesity treatment is not known.…”
Section: Introductionmentioning
confidence: 99%
“…21 Through an assessment of PwO, HCPs and employer representatives, the ACTION study demonstrated that although generally perceived as a disease, obesity is not commonly treated as such. 21 Through an assessment of PwO, HCPs and employer representatives, the ACTION study demonstrated that although generally perceived as a disease, obesity is not commonly treated as such.…”
Section: Introductionmentioning
confidence: 99%